Ultrasensitive negative capacitance phototransistors - Luqi Tu (Nature Portfolio, 2020)
Here, the authors report ultrasensitive negative capacitance phototransistors based on MoS2 regulated by a layer of ferroelectric hafnium zirconium oxide film to demonstrate a hysteresis-free ultra-steep subthreshold slope of 17.64 mV/dec and specific detectivity of 4.75 × 1014 cm Hz1/2 W−1 at room temperature.